The History of Helminths, Helminthology and the Discoveries of Scientists Who Have Done Scientific Research with This Disease - Nurislomova Latofatoy Fazliddin Qizi (Zien Journals, 2023)
This article discusses the history of helminths, helminthology, and the discoveries of scientists who have done scientific research with the disease
Keywords: Helminths; helminths; helminths in children and adolescents